Legal Reconstruction of Guarantee Institutions In Online Loan Disputes without Collateral - Restianti, Riza; Wardiono, Kelik (Jurnal Ius Constituendum, 2025)
Riza Restianti, Kelik Wardiono Faculty of Law and Political Science, Muhammadiyah University of Surakarta, Surakarta, Indonesia c100210168@student.ums.ac.id   Abstract   This study analyzes the juridical implications of Decision No. 150/Pdt.G/2021/PN Cbi concerning the legal status of guarantee institutions in online loan disputes and their impact on legal protection and certainty. The absence of valid collateral in fintech-based lending has led to an increasing number of disputes, weakening creditors’ legal standing and contractual enforcement. This research aims to evaluate how the court’s interpretation in this decision reshapes the validity and enforceability of guarantees in digital lending contracts. Using a normative juridical method supported by qualitative analysis of legislation and judicial reasoning, the study explores the court’s assessment of unsecured lending practices within the framework of civil law principles. The results indicate that the decision underscores the necessity of verifiable and enforceable collateral mechanisms to protect creditors’ rights while maintaining fairness for debtors. Furthermore, the study highlights the urgency of reforming digital credit agreements to include structured verification and legal compliance mechanisms that uphold both transparency and contractual balance. The novelty of this research lies in its critical reconstruction of guarantee validity in online loan arrangements through the lens of judicial precedent, contributing to the development of civil law and fintech governance in Indonesia. The findings provide normative recommendations for policymakers to strengthen legal certainty, accountability, and consumer protection in digital financial transactions.